2014
DOI: 10.1111/beer.12060
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility perception in business students as future managers: a multifactorial analysis

Abstract: This paper examines undergraduate business students' perception of corporate social responsibility (CSR) in cases in which they have not attended any specific course either dealing with CSR or providing training in ethics. A survey was conducted of 535 Spanish business students as future managers. The results show that the stakeholders' perspective deserves a huge attention for those students considering what the keys of business success are. Significant differences in perception were nevertheless identified w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 62 publications
6
70
1
3
Order By: Relevance
“…This study will also expand on the existing research, which has shown, on the whole, that stakeholders with different individual characteristics (such as gender, age and educational level) can also experience different levels of CSR perceptions and expectations, and, more generally, CSR attitudes (e.g. Alonso‐Almeida, Fernández de Navarrete, & Rodriguez‐Pomeda, ; Burton & Hegarty, ; Lämsä, Vehkaperä, Puttonen, & Pesonen, ).…”
Section: Introductionmentioning
confidence: 89%
“…This study will also expand on the existing research, which has shown, on the whole, that stakeholders with different individual characteristics (such as gender, age and educational level) can also experience different levels of CSR perceptions and expectations, and, more generally, CSR attitudes (e.g. Alonso‐Almeida, Fernández de Navarrete, & Rodriguez‐Pomeda, ; Burton & Hegarty, ; Lämsä, Vehkaperä, Puttonen, & Pesonen, ).…”
Section: Introductionmentioning
confidence: 89%
“…Females were also observed as being more likely to follow a stakeholder model than a shareholder model. Similarly, Alonso-Almeida et al (2015a) found that women place higher priority than men on CSR issues. Marz et al (2003) again showed that female respondents express a higher social responsibility than male respondents.…”
Section: Gender Difference In Ethics Business Ethics Csr and Sustaimentioning
confidence: 98%
“…Many research studies have shown that women are more sensitive to corporate social responsibility issues and give high importance to social issues as compared to men (Alonso‐Almeida, Fernández de Navarrete, & Rodriguez‐Pomeda, ). As women more commonly display voluntary behavior and engage in charity issues, green behavior both task related and voluntary is strongly expected of them.…”
Section: Theoretical Framework and Research Propositionsmentioning
confidence: 99%